CAMPUR KODE DALAM INTERAKSI MASYARAKAT DESA BOLADANGKO KECAMATAN KULAWI KABUPATEN SIGI - Ferdiawan (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) IAIN Palu, 2020)
Based on the formulation of the problem of this research is how the form of code mixing in the interaction of Boladangko village community in the Kulawi district of Sigi district and the factors driving the code mix in the Community Interaction of Boladanko Village in the Kulawi District of Sigi district. The purpose of this study was to determine the form of mixed code speech in the interaction of Boladanko village, Kulawi sub-district, Sigi district. The method used in this study is a qualitative method. Qualitative research methods are intended to describe the form of mixed code speech in the Boladangkokececity of Kulawi Sub-district, Sigi Regency. Based on the results of the study the authors found a mixture of the Kaili language code (Moma) and Indonesian. Mix the code because the speaker forgets the language of his area so that the speaker sometimes deliberately interferes with the code because of the habits and the ease of speech and changes in the way of communication between the speaker and the interlocutor. The following is code mixing data that occurs in the process of community interaction in Boladangko Village, Kulawi Subdistrict, Sigi Regency based on word class, namely, insertion of affixed elements, insertion of elements in the form of clauses, insertion of elements in the form of words and insertion of elements in the form of phrases. The driving factor for code mixing has more to do with the speaker, the speech partner, the function and purpose of the speaker, and the situation of the conversation. The driving factors for code mixing are extralinguistic and intralinguistic factors. Extralinguistic factors related to the character of the speaker such as background, social, religious sense, level of education, and regionalism. Intralinguistic factors relate to the absence of words in the Moma language that are capable of overseeing the concept referred to as the linguistic element that is inserted.